Asymmetry in Measurements near Light Speed - Pieters, Cornelis Pieter (London Journal of Physics, 2024)
The intentions of this theoretical exercise are two-fold. Firstly, the relationship between measurement and the theory or hypothesis that is tested is discussed as a methodological challenge. It is argued that measurements will always lead to multiple explanations of the data. Secondly the consequences of this stance are explored with measurements of objects moving with high velocities. The generally accepted equations of such objects are mirrored with an alternative interpretation, that is based on 'deconstructing' the way that such measurements are carried out. More specifically, this contribution concentrates on asymmetry in point measurements, which are measurements that are conducted from one spatial location. As many measurements require multiple samples, this may imply that consecutive measurements move with respect to the measuring device. This may cause an asymmetry, or myopia, in the data that is collected. Such measurements should therefore be corrected for the corresponding effects. This article will give a theoretical description of the myopia in point measurements specifically for objects moving with high velocity, in particular near the speed of light. It is demonstrated that the results are in correspondence with the equations that are commonly used to describe the velocities of such particles, such as the Lorentz transformations or the energy-momentum relationship, although the interpretation of these outcomes are somewhat different.